The Arabic Language as A Basic Epistem in The Scientific Tradition of Islamic Boarding School Education - Tabroni, Imam; Naufal Irsyadi, Achmad; Kartiko, Ari; Rutumalessy, Merlyn; Dessye Parinussa, Jolanda (International Journal of Educational Research & Social Sciences, 2022)
The yellow book (kitab kuning) is the basic curriculum in Islamic boarding school education. He uses Arabic as an instrument of presentation. So, the educational process of pesantren is definitely in contact with Arabic as an episteme in its scientific building. This study aims to describe the Arabic language as a fundamental epistem in Islamic boarding school education and its relation to the scientific construction of Islamic boarding schools based on it. This research is a qualitative research with the type of literature study. This study uses data collection methods in the form of documentation of all libraries related to Islamic boarding schools and the Arabic language. Then, the data analysis used is descriptive analysis and content analysis. In testing the validity of the data, the researcher used triangulation, namely source triangulation, method triangulation, peer discussion and member check. The results of this study are: 1) The episteme of the pesantren scientific tradition is the Bayani epistem which is based on Arabic in aqidah and shari'ah Islamiyah. 2) Arabic that is learned in Islamic boarding school education begins with theoretical Arabic which is oriented to the practice of reading the yellow book as the basic curriculum in Islamic boarding school learning.